EFFECTIVENESS OF CLAY PLASTICINE PLAY THERAPY ON FINE MOTOR DEVELOPMENT IN CHILDREN - erlina suci astuti (STIKes Kepanjen, 2022)
Fine motor development in children aged 3-5 years is very fundamental for the next child's life. Periods like this are the first basic period in developing potential, attitudes, skills and creativity. The preliminary study conducted on June 6-24 2022 at Pelita Hati Malang PAUD aims to find out how much influence it has on the fine motor development of children by using the plasticine clay method. This research method is a quantitative experimental research with a quasi-experimental research method with a pre-test and post-test research design with control group design. The sampling technique uses a simple random sampling technique. Sampling consisted of 30 respondents divided into 2 groups, namely the treatment and control groups. Data analysis used the Wilcoxon test and the Man Whitney test. The statistical test results showed Asymp.Sig (2-tailed) of 0.035 <0.05. It can be concluded that the difference in results between the treatment group and the control group. Because there is a significant difference, it can be said that there is an influence in the use of clay plasticine playing methods on children's fine motor development. Some suggestions that can be recommended are the development of Human Resources (HR) through changes in planning in learning and selecting learning methods so that in delivery. All aim so that effectiveness can be realized in the development of children's fine motor skills.